Contribution of binge eating behaviour to cardiometabolic risk factors in subjects starting a weight loss or maintenance programme. Issue 11 (15th December 2016) - Leone, Alessandro; Bedogni, Giorgio; Ponissi, Veronica; Battezzati, Alberto; Beggio, Valentina; Magni, Paolo; Ruscica, Massimiliano; Bertoli, Simona
Abstract: The contribution of binge eating (BE) behaviour to cardiometabolic risk factors has been scarcely investigated so far. Previous studies have not considered the nutritional status and lifestyle of subjects suffering from BE. The aim of this study was to evaluate the contribution of BE to the metabolic syndrome (MS), its components, high total cholesterol and high LDL in a large sample of subjects, taking into account nutritional status, dietary habits, smoking status and physical activity. For this purpose, 5175 adults seeking a weight loss or maintenance programme were recruited. Anthropometrical measurements and blood parameters were measured. BE was evaluated using the Binge Eating Scale (BES). A fourteen-item questionnaire was used to evaluate the adherence to the Mediterranean diet. Smoking status and physical activity were investigated by interview. BE prevalence was 0·16 (95 % CI 0·15, 0·17). A sex- and age-adjusted Poisson regression model showed a higher prevalence of MS in binge eaters (0·33; 95 % CI 0·28, 0·37) compared with non-binge eaters (0·27; 95 % CI 0·25, 0·28, P =0·011). However, the statistical difference was lost after inclusion of BMI and lifestyle parameters in the multiple-adjusted model. We also evaluated the association between the continuous outcomes of interest and the BES score using a multivariable median regression model. We observed a positive, but clinically irrelevant, association between BES score and HDL levels ( P <0·001). In conclusion, BE does not seem to be independently related to cardiometabolic risk factors. However, the screening and treatment of BE are of clinical relevance in order to reduce the risk of developing obesity.